Anthropological Aspects of Alcohol Trade in Microsocieties of Chukotka National Settlements - Anastasiya Yarzutkina (Journal of Ethnology and Folkloristics)
The aim of the report is to describe the communicative culture that has been established between the home-made vodka traders (home-distilled vodka producers), alcohol buyers and activists fighting for temperance in national settlements of Chukotka. Informal economic relations take place within particular settlements; the main thing that is involved in these relations is alcohol. Outside the settlement the connections between traders and buyers do not work and the network of interactions breaks. To mark out the participants in the alcohol trade the report presents the structure of settlement microsociety in Chukotka from a very generalised perspective, based on author's experience of staying in these settlements and on some statistical data.